Bentuk, Makna, dan Fungsi dalam Mantra Pengobatan Dukun di Kabupaten Lamongan (Kajian Etnolinguistik) - Abdullah Syarofi (Al Yazidiy Jurnal Sosial Humaniora dan Pendidikan, 2022)
Paper is aimed to describe and explain the form, meaning, and function of Lamongan dukun’s (Indonesian shaman) spell in healing the patient. The research method used in this article is observation approach. In this research, the researcher involves himself as an audience when the dukun cast his spell to his patient. The researcher recorded the interviews with the Dukun. In addition, this study also uses literary data from books, papers, internet, thesis, journal, and any other sources that support the research. In analyzing the data, the researcher decided to classify the data into form, meaning, and function. The ‘form’ data is analyzed using poetry structure theory. The ‘meaning’ data is analyzed using semantic approach. The ‘function’ data is analyzed using Malinowski theory. There are two results of the ‘form’ analysis, which are: Seloka and Bidal. From the ‘function’ analysis, there are three functions, which are: (1) For a healing spell; (2) To pray to Allah SWT; (3) and as a medium to bring evil and good. The ethnolinguistic analysis of this research focused on the process of language dimension in cultural dimension of a Dukuns’ ritual in casting his spell to his patient.